Assessing Italian household preferences for waste sorting systems: The role of environmental awareness, socioeconomic characteristics, and local contexts. (15th May 2023) - Cantillo, Tatiana; Notaro, Sandra; Bonini, Nicolao; Hadjichristidis, Constantinos
Highlights: Non-utilitarian factors shape individual's WTP for WMS improvements. Environmental values are key predictors of WTP for improved WMS. Preferences for WMS are determined by environmental and local contexts. Socioeconomics' impact on WMS preferences through environmental values is weak. Effective WMS policy making must be context-specific. Abstract: Efficient Waste Management Systems (WMS) depend on citizens' willingness to sort waste and to cooperate for its improved provision. Thus, it is essential to understand what attributes individuals value the most and what drives WMS preference heterogeneity. In this paper, we investigate how individuals evaluate WMS attributes (e.g., the number of waste sorting categories, the introduction of textile sorting, and the frequency of collection per week) and how the local contexts, socioeconomics, and environmental values shape their preferences. For this purpose, we conducted a discrete choice experiment on a sample representative of the Italian population interviewed through an online panel survey. We collected information on individual's preferences for WMS attributes, environmental awareness, and socioeconomic characteristics. We analyzed the data using hybrid mixed choice models, which allowed us to integrate environmental awareness values into willingness to pay estimations. We found that individuals are willing to pay for waste sorting, even if this implies more effort on their part and increased storage space. In addition, we found that the extent to which individuals support WMS improvements strongly depends on their environmental values, experiences (which are shaped by their local context), and socioeconomic factors. Our results suggest that to increase recycling rates and citizen satisfaction, there is a need for context-specific WMS designs that acknowledge the observed heterogeneity of preferences.